Clonal Propagation and Reproductive Biology in Jatropha curcas L. - Dhillon, R.S.; Hooda, M.S.; Handa, A.K.; Ahlawat, K.S.; Kumar, Y.; Kumar, Subhash; Singh, N. (Indian Journal of Agroforestry, 2020)
Effect of auxins (IM, IBAand NM) and vitamin B2(Thiamine), on rooting response of branch cuttings of Jatropha curcas showed maximum success in sprouting and rooting characters of cuttings planted during spring season. Even the untreated (control) cuttings showed 100 per cent sprouting in spring. The cuttings treated with thiamine (250, 1000, 1500, 2000 ppm) triggered maximum sprouting in both seasons. Maximum per cent rooting 96.5 and 66.6 was induced in 2000 ppm IBA treated cuttings in spring and monsoon seasons, respectively. The minimum rooting percentage in both the seasons was recorded in 2000 ppm NM treatment. However, highest number of roots per cutting (73.2 and 34.6) exhibited in cuttings treated with 1500 ppm IBA. The study in relation to reproductive biology showed that bud began to appear as small protruding structure intermingled with the initiation of new leaves at the terminal end of branches. Majority of plants flower after rainy season i.e. in September-October however, some plants flower even in spring season (March- April). Flowers are unisexual, male and female flower produced in the same inflorescence. The average male to female flower ratio was 20:1, which changed drastically (108:1) with the fall in temperature. The male floral buds develop earlier than female. The flowering pattern was asynchronous. The peak period of flowering varied from 3-20 days. Period of fruit development and maturity ranged from 55 to 61 days. The results of breeding system indicated 32.9 per cent fruit setting under selfing and 89.7 per cent under natural pollination. The high fruit setting under open pollination revealed that the plant is capable of producing fruits through selfing (geitonogamy) and open pollination (xenogamy) such a breeding system represents Â facultative cross pollination.